IMPLEMENTASI PERATURAN MENTERI DESA PEMBANGUNAN DAERAH TERTINGGAL DAN TRANSMIGRASI REPUBLIK INDONESIA NOMOR 11 TAHUN 2019 TENTANG PENGGUNAAN DANA DESA TAHUN 2020 DI DESA KELAPA DUA KECAMATAN SELAT PENUGUAN KABUPATEN BANYUASIN - Suryani, Riza Adelia (Jurnal Ilmiah Administrasi Dan Sosial, 2023)
Financing or finance is essential in supporting the implementation of village autonomy, as well as in the implementation of regional autonomy which says that "autonomy" is synonymous with "automatic money", so to regulate and manage its own household the village requires funds or adequate as required implementation support. Implementation of support within the framework of this authority, in Law Number 6 of 2014 villages are given sources of income originating from seven sources The method used is a qualitative method, data collection techniques are carried out by means of observation, interviews with parties involved in becoming research informants, library research, documentation, and data analysis techniques The results of the research on the implementation of the Regulation of the Minister for Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia Number 11 of 2019 concerning the Use of Village Funds in 2020 in Kelapa Dua Village, Selat Penuguan District, Banyuasin Regency based on his research, where from the four implementation theories, the author can conclude that the Behavior of Implementing and Bureaucratic inthe Fund Program This village has been running well, because the two indicators have been implemented in accordance with applicable regulations, while Communication and Human Resources have not been so good in their implementation. Likewise, the principles and priorities for using the Village Fund are implemented in Kelapa Dua Village. In  principle, the use of Village Funds in Kelapa Dua Village has been implemented properly, several principles of using Village Funds have been implemented in accordance with applicable procedures and rules, for example by implementing development that includes all levels of society with the aim that development can be felt by all levels of society. Likewise, the priority of using the Village Fund for village development, which is more emphasized in the field of development in the field of facilities and infrastructure that supports village community activities, as well as empowering village communities who are recipients and implementers of the Village Fund program.